Error analysis of the p-version discontinuous Galerkin method for heat transfer in built-up structures - Hideaki Kaneko (2018)
In this paper, we provide an error analysis for the p-version of the discontinuous Galerkin finite element method for a class of heat transfer problems in built-up structures. Also, a general form of the matrix associated with the discretization of time variable using the p-finite element basis functions is established. Many interesting properties of this matrix are obtained. Numerical examples are provided in the last section.